Obtenção de fibra de vidro recoberta como dispositivo de microextração em fase sólida para determinação de solventes residuais por cromatografia gasosa (CG) - Ilipronti, Thiago (2017)
In this work, glass fibers have been used as support for the decomposition of a Zinc Oxide (ZnO) layer and a Zeolitic-Imidazolate Framewoks-8 (ZIF-8) layer, both for the application of Solid Phase Micro-Extraction (SPME) technique. The coating ZnO fiber was obtained by dip coating technique in and by using zinc nitrate and hexamethylenetetramine as precursor reagents of the ZnO. The synthesis of ZIF-8 was used the 2-methylimidazole as precursor. The fibers were characterized by Electron Microscopy Scanning (SEM) to evaluate their morphology of fibers without coating, fibers with zinc oxide coating and fibers with ZIF-8 coating. The X-ray Diffraction (XRD) technique has allowed attaining the diffraction standard of the ZnO and ZIF-8 crystals. Thermogravimetric analysis (TGA) was performed to evaluate the thermal stability of ZnO and ZIF-8, indicating thermal stability around 400 °C. The SEM results indicated that the synthesis method in methanolic medium has presented a homogenous and regular coating of the ZnO layer in nanorods shape and, for the ZIF-8 synthesis, the Framework-8 net formation. As such, the ZnO coated fibers were used in the methanolic medium to the application of the SPME technique by using a Headspace sampler (HS) coupled to a gas chromatograph with flame ionization detection (GC-FID) in the chromatographic determination of the following residual solvents: Acetone, dichloromethane, methanol, butanol and ethyl acetate. The method optimization was performed in the chromatographic step, in which four parameters were tested: the incubation temperature, incubation time, extraction/ sorption time and desorption time. The obtained values were 70 °C, 10 minutes, 1 minute and 4 minutes, respectively. After methods optimization, the analytical methodology validation was performed to determine the solvents (quantify the solvents). The method was shown to be specific, absence of coelution between the analytes studied. For the linearity in the concentration interval from 5,99 to 299,93 µg mL-1 the correlation coefficient (R) was 0,9938, 0,9983, 0,9988 and 0,9982 for methanol, butanol, dichloromethane and ethyl acetate, respectively. The method has shown precision and accuracy in the recovery interval, from 80 to 120%, presenting Relative Standard Deviation (RSD) not more than 15% in all determination levels 1 (20%), 4 (80%) and 6 (120%). The method has also presented Robustness and a large potential for residual solvents determination.